Tuning the thermoelectric properties of a single-molecule junction by mechanical stretching1. Issue 7 (21st February 2015) - Torres, Alberto; Pontes, Renato B.; da Silva, Antônio J. R.; Fazzio, Adalberto
<x xml:space="preserve">Abstract</x> We theoretically investigate, as a function of the stretching, the behaviour of the Seebeck coefficient, the electronic heat conductance and the figure of merit of a molecule-based junction composed of a benzene-1, 4-dithiolate (BDT) molecule coupled to Au(111) surfaces at room temperature.